Cytotoxic necrotizing factor 1 promotes bladder cancer angiogenesis through activating RhoC. Issue 6 (21st April 2020) - Guo, Yaxiu; Wang, Jingyu; Zhou, Kaichen; Lv, Junqiang; Wang, Lei; Gao, Shan; Keller, Evan T.; Zhang, Zhi‐Song; Wang, Quan; Yao, Zhi
Abstract: Uropathogenic Escherichia coli (UPEC), a leading cause of urinary tract infections, is associated with prostate and bladder cancers. Cytotoxic necrotizing factor 1 (CNF1) is a key UPEC toxin; however, its role in bladder cancer is unknown. In the present study, we found CNF1 induced bladder cancer cells to secrete vascular endothelial growth factor (VEGF) through activating Ras homolog family member C (RhoC), leading to subsequent angiogenesis in the bladder cancer microenvironment. We then investigated that CNF1‐mediated RhoC activation modulated the stabilization of hypoxia‐inducible factor 1α (HIF1α) to upregulate the VEGF. We demonstrated in vitro that active RhoC increased heat shock factor 1 (HSF1) phosphorylation, which induced the heat shock protein 90α (HSP90α) expression, leading to stabilization of HIF1α. Active RhoC elevated HSP90α, HIF1α, VEGF expression, and angiogenesis in the human bladder cancer xenografts. In addition, HSP90α, HIF1α, and VEGF expression were also found positively correlated with the human bladder cancer development. These results provide a potential mechanism through which UPEC contributes to bladder cancer progression, and may provide potential therapeutic targets for bladder cancer.